Desenvolvimento de um instrumento virtual de avaliação da fala - Uberti, Letícia Bitencourt (2023)
This study aimed to develop a Virtual Speech Assessment Tool to evaluate the speech production of children and adolescents who speak Brazilian Portuguese. This tool was based on a Dutch speech assessment tool that presents various speech stimuli (picture naming, word and non-word repetition and imitation, and diadochokinesis), as well as two other Brazilian tools (a phonological and motor speech assessment). The developed web system enables the evaluation of speech production in children and adolescents who speak Brazilian Portuguese through different forms of verbal elicitation. This tool allows speech therapists to obtain a more specific diagnosis for Speech Sound Disorders. The development of the tool was organized into nine stages: Stage 1 - Analysis of instruments and task definition; Stage 2 - Stimulus selection; Stage 3 - Analysis by expert judges; Stage 4 - Semantic analysis; Stage 5 - Illustration of words; Stage 6 - Analysis by non-expert judges; Stage 7 - Development of the web system; Stage 8 - Pilot study 1; Stage 9 - Pilot study 2. The stimuli used in the tool underwent analysis by expert judges, semantic analysis, and analysis by non-expert judges, resulting in 91 words and 26 nonwords. Speech therapists with a doctorate degree in speech assessment, as well as children and adolescents from different regions of Brazil aged from two to 17 years and 11 months, participated as judges in these stages. Therefore, it was demonstrated that the instrument presented in this study has appropriate content validity for its purpose. After the illustration of words, recording of videos and audios, and development of the web system, Pilot Study 1 was carried out, which included one child and one adolescent with typical speech development. In this stage, modifications were made to the tool in order to reduce the time taken to administer the word naming and imitation test and to prevent fatigue. Therefore, the list of 91 words was reorganized according to the number of phonemes in different positions in the word for the naming and imitation tests. In the end, the tool included: 91 real words (61 words for naming, 51 for imitation, and 5 words for repetition); 26 non-words (26 for imitation and 4 for repetition); and 6 stimuli for the diadochokinesis test. In Pilot Study 2, 32 children and adolescents aged from two to 17 years and 11 months, with typical speech development and previously diagnosed Speech Sound Disorders, were evaluated using the Virtual Speech Assessment Tool. In this stage, some words were found to be difficult for younger children and the list of cues was revised and modified. Additionally, participants reported a decrease in fatigue and expressed enjoyment with the tool, finding the pictures and format appealing. In tasks involving imitation of non-words, repetition of words and non-words, and diadochokinesis, the participants did not have difficulty and understood the instructions. The tool presents variation in terms of administration time, depending on the age of the participant, but on average, it takes around 30-40 minutes to administer the entire assessment.